Methyl jasmonate promotes anthocyanins' production in Prunus salicina × Prunus persica in vitro shoot cultures. (3rd September 2017) - Lucioli, S.; Di Bari, C.; Nota, P.; Frattarelli, A.; Forni, C.; Caboni, E.
Abstract: In vitro shoot cultures of Prunus salicina  ×  Prunus persica, "Citation®" rootstock, were treated with 50-μM methyl jasmonate (MJ) or 100-μM abscisic acid (ABA); in MJ-treated shoots, total anthocyanins increased significantly (1.88 mg/g fresh weight) relative to controls (0.43 mg/g fresh weight). Cyanidin 3-glucoside was the most abundant anthocyanin in both MJ-treated and control explants. The addition of ABA to the culture medium did not elicit anthocyanins' accumulation.